Image Edge Sharpening Pada Sketsa Gambar Menggunakan Metode Haar Wavelet - Ardiwinata Ardiwinata (Bulletin of Information System Research, 2023)
A sketch is a simple drawing or rough draft that depicts the main parts without details. A sketch drawing is an initial idea drawing to express certain ideas into a design drawing summarizing aspects of the initial drawing design that require further processing. Sketch drawing is basically drawing lines with a free hand, without the help of a ruler. In drawing this sketch, sometimes the lines produced on the object edges are not very bright, and require sharpening on each edge of the object. For this reason, sharpening is also done on the edges of the object to make it look sharper on the edges of the object. This image sharpening is useful so that it can be interpreted by the human eye. In the process of working on this thesis, the software used is MATLAB. MATLAB is one of the software with a high level programming language. The final result of this thesis is an object with sharpened edges. In the thesis work using the Haar Wavelet method.